All Days 2010
DOI: 10.2118/138806-ms
|View full text |Cite
|
Sign up to set email alerts
|

Surface Microseismic Mapping Reveals Details of the Marcellus Shale

Abstract: The mapping of microseismic events induced by hydraulic fracturing plays an important role in well completion and design. This is especially true in a newly developing area of gas producing shales. In this case study, we will show how the microseismic monitoring of a hydraulic fracture treatment in the Marcellus Shale identified a pre-existing natural fault which intersected the wellbore. The data from nearby wells indicated several possibilities of structural evolution affecting the producing formation. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…As such, it is used as a diagnostic tool for hydraulic fracturing treatments to infer the approximate extent and the orientation of the final fracture(s) [ Rutledge et al , ; Maxwell et al , ]. Few documented cases of the HF intersecting and potentially propagating along a well‐developed fault (scenario (1) and (2i) in the above) within the hydraulically fractured reservoir [ Hulsey et al , ; Wolhart et al , ] showed a tendency for increased count and magnitude of events associated with the reservoir fault yet still remaining within the microseismic realm (negative seismic moment magnitude).…”
Section: Field Implicationsmentioning
confidence: 99%
“…As such, it is used as a diagnostic tool for hydraulic fracturing treatments to infer the approximate extent and the orientation of the final fracture(s) [ Rutledge et al , ; Maxwell et al , ]. Few documented cases of the HF intersecting and potentially propagating along a well‐developed fault (scenario (1) and (2i) in the above) within the hydraulically fractured reservoir [ Hulsey et al , ; Wolhart et al , ] showed a tendency for increased count and magnitude of events associated with the reservoir fault yet still remaining within the microseismic realm (negative seismic moment magnitude).…”
Section: Field Implicationsmentioning
confidence: 99%
“…Case 2,-The second case is a vertical hydraulic fracture created in a horizontal gas well drilled in the Marcellus shale. The microseismic monitoring data for hydraulic fracturing stage 5 was published by Hulsey et al (2010). However there were 6 hydraulic fracturing stages.…”
Section: Case Studiesmentioning
confidence: 99%
“…Discrete fracture networks often link microseismic event trends to pre-existing fault reactivation and the orientation of S Hmax (Maxwell et al 2002, Hulsey et al 2010. These patterns are also characteristic of the Barnett Shale, in which the study took place (Gale et al 2007).…”
Section: Introductionmentioning
confidence: 99%